Self-Motivation Is Associated With Phosphorus Control in End-Stage Renal Disease - Umeukeje, Ebele M; Merighi, Joseph R; Browne, Teri; Victoroff, Jacquelyn N; Umanath, Kausik; Lewis, Julia B; Ikizler, T Alp; Wallston, Kenneth A; Cavanaugh, Kerri (Journal of renal nutrition, 2015)
Hyperphosphatemia is common in end-stage renal disease and associates with mortality. Phosphate binders reduce serum phosphorus levels; however, adherence is often poor. This pilot study aims to assess patients' self-motivation to adhere to phosphate binders, its association with phosphorus control, and potential differences by race. Cross sectional design. Subjects were enrolled from one academic medical center dialysis practice from July to November 2012. Self-motivation to adhere to phosphate binders was assessed with the autonomous regulation (AR) scale (range: 1-7) and self-reported medication adherence with the Morisky Medication Adherence Scale. Linear regression models adjusting for age, sex, health literacy, and medication adherence were applied to determine associations with serum phosphorus level, including any evidence of interaction by race. Among 100 participants, mean age was 51 years (±15 years), 53% were male, 72% were non-white, 89% received hemodialysis, and mean serum phosphorus level was 5.7 ± 1.6 mg/dL. More than half (57%) reported the maximum AR score (7). Higher AR scores were noted in those reporting better health overall (P = .001) and those with higher health literacy (P = .01). AR score correlated with better medication adherence (r = 0.22; P = .02), and medication adherence was negatively associated with serum phosphorus (r = -0.40; P < .001). In subgroup analysis among non-whites, higher AR scores correlated with lower serum phosphorus (high vs lower AR score: 5.55 [1.5] vs 6.96 [2.2]; P = .01). Associations between AR score (β 95% confidence interval: -0.37 [-0.73 to -0.01]; P = .04), medication adherence (β 95% confidence interval: -0.25 [-0.42 to -0.07]; P = .01), and serum phosphorus persisted in adjusted analyses. Self-motivation was associated with phosphate binder adherence and phosphorus control, and this differed by race. Additional research is needed to determine if personalized, culturally sensitive strategies to understand and overcome motivational barriers may optimize mineral bone health in end-stage renal disease.